Low -cost photovoltaic back sheet - ZHOU XIN; HUANG JIANBING; HUANG JIANQUAN (2018)
The utility model relates to a low -cost photovoltaic back sheet, including PET basic unit, first adhesive layer, fluorine rete, second adhesive layer, coat and protective layer, the upper surface ofPET basic unit passes through first adhesive layer with the fluorine rete is connected, the lower surface of PET basic unit passes through the second adhesive layer with the coat is connected, the surface coating matcoveredn of fluorine rete. The utility model discloses a low -cost photovoltaic back sheet cost of manufacture is hanged down, is all had outstanding performance in the aspect of ageing -resistant, model performance, separation steam, and the price / performance ratio is than higher. 本实用新型涉及种低成本光伏背板，包括PET基层、第胶粘层、氟膜层、第二胶粘层、涂覆层和保护层；所述PET基层的上表面通过所述第胶粘层与所述氟膜层连接；所述PET基层的下表面通过所述第二胶粘层与所述涂覆层连接；所述氟膜层的外表面涂覆有保护层。本实用新型的低成本光伏背板制作成本低、在耐老化、机型性能、阻隔水汽方面都具有优秀的性能，性价比比较高。